Patient and physician perspectives on treatment burden in end-stage kidney disease: a nominal group technique study. Issue 12 (5th December 2022) - Thomas, Sarah T; Sav, Adem; Thomas, Rae; Cardona, Magnolia; Michaleff, Zoe; Titus, Thomas T; Dobler, Claudia C
Abstract : Objectives: The treatment workload associated with end-stage kidney disease (ESKD) is high. The treatment burdens experienced by patients with ESKD are not well understood. In this study, we aimed to elucidate the most important areas of treatment burden for discussion in a clinical encounter from the perspectives of patients with ESKD and nephrologists. We sought to explore possible solutions to these high priority treatment burden challenges. Design: Nominal group technique (NGT) sessions. Setting and participants: Three in-person NGT sessions were conducted with 19 patients with dialysis-dependent ESKD from one tertiary treatment centre (mean age 64 years; range 47–82). All patients were either retired or on a disability pension; 74% perceived moderate or severe treatment burden; and 90% spent more than 11 hours on treatment-related activities per week (range 11–30). One online NGT session was conducted with six nephrologists from two Australian states. Main outcome measures: The primary outcome was a ranked list of treatment burden priorities. The secondary outcome was potential solutions to these treatment burden challenges. Results: Every patient group ranked health system issues as the most important treatment burden priority. This encompassed lack of continuity and coordination of care, dissatisfaction with frequent healthcare encounters and challenges around healthcare access. Psychosocial burdens on patients and families were perceived to be the most important area of treatment burden by physicians, and were ranked the second highest priority by patients. Conclusions: Discussing treatment burden in a clinical encounter may lead to a better understanding of patients' capacity to cope with their treatment workload. This could facilitate tailored care, improve health outcomes, treatment sustainability and patients' overall quality of life.